برامج تعليم الخط العربي في معهد ابن البواب الخطي في ماديون إندونيسيا - Abdul Muntaqim Al Anshory; Muhamad Rizal Falaqi (Journal of Calligraphy, 2023)
This study aims to describe Arabic calligraphy learning programs at the "Ibn Al-Bawwab" Calligraphy School in Madiun, and the supporting and inhibiting factors. This research is a qualitative descriptive study. Sources of data used are school administrators and documents. To collect data, researchers used observation, interviews, and documentation with qualitative data analysis methods: data reduction, presentation, and drawing conclusions. The results of this study are: 1) The objectives of the program are to spread Islam, form a generation of the Qur'an, get used to writing the Qur'an well and beautifully, be creative and innovative in developing calligraphy. The learning strategy used is 'tadrib'. The learning material consists of writing calligraphy and making calligraphy with ornaments. It opens with offline and online learning, and ends with an evaluation. 2) The supporting factors are experienced and reputable teachers in calligraphy, convenient location, and the number of programs provided. The inhibiting factors are the difficulty of achieving learning objectives for some students, the absence of students or teachers, and the distance.يهدف هذا البحث وصف برامج تعليم الخط العربي في معهد "ابن البواب" الخطي بماديون، والعوامل الداعمة والمثبطة لها. هذا البحث بحث وصفي كيفي. مصادر البيانات المستخدمة هي رجال المعهد والوثائق المعهدية. ولجمع البيانات استخدم الباحث الملاحظة، والمقابلة، والوثائق بطريقة تحليل البيانات الكيفية: تقليل البيانات وعرضها والاستنتاج. نتائج هذا البحث هي: 1) الأهداف من البرامج هي نشر الإسلام، وتكوين جيل قرأني، والتعود على كتابة القرآن بشكل جيد وجميل، والإبداع والابتكار لتطوير الخط. استراتيجية التعليم المستخدمة هي "التدريب". المواد التعليمية فيها تتمثل في نشاطان رئيسيان، وهما كتابة الخط وإعداد أعمال الخط (بالزخرفة). كانت البرامج مفتوحة بالتعليم في الحجرة الدراسية والتعليم عبر الإنترنت وتنتهي بالتقويم. 2) العوامل الداعمة هي: المعلمون ولهم خبرات ومتميزون في الخط، وموقع المعهد الملائم، وعدد البرامج. أما العوامل المثبطة فهي صعوبة تحقيق أهداف التعليم لبعض التلاميذ، وغياب التلاميذ أو المعلمين في بعض الأحيان، ومسافة المعهد.